Exercise intensity does not affect the composition of diet- and exercise-induced body mass loss - Ballor, D. L.; McCarthy, J. P.; Wilterdink, E. J. (The American Journal of Clinical Nutrition, 1990)
The effect of caloric restriction (1200 kcal/d intake) in combination with high (High) (80-90% of peak VO2) or low (Low) (40-50% of peak VO2) exercise work rates on the composition of lost body mass was determined in 27 obese women (percent fat, 36.7 +/- 4.2%; mean +/- SD). All subjects trained 3 d/wk for 8 wk, with the High (n = 14) and Low (n = 13) groups exercising for 25 and 50 min/d, respectively. After posttesting there were no differences between the groups with respect to pre- to posttest changes (mean of combined groups) in body mass (-7%), fat-free mass (-10%), fat mass (-16%), percent fat (-10%), and sum of five skinfold-thickness measurements (-16%). This study suggests that with regard to conservation of fat-free mass, the selection of an exercise intensity for a diet and exercise regimen may be left to the preference of the clinician and/or dieter.